2018
DOI: 10.1177/0361198118787374
|View full text |Cite
|
Sign up to set email alerts
|

Monte Carlo Simulation-Based Benefit-Cost Analysis Combined with Analytical Hierarchy Process to Support ITS Investment with Consideration of Connected Vehicle Technology

Abstract: Decisions to invest in alternative intelligent transportation system (ITS) technologies are expected to increase in complexity, particularly with the introduction of connected vehicles (CV) and automated vehicles (AV) in the coming years. Traditional alternative analyses based on deterministic return on investment analysis are unable to capture the risks and uncertainties associated with the investment problem. In addition, these methods cannot account for agency preferences and constraints that cannot be conv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
(20 reference statements)
0
5
0
Order By: Relevance
“…Past studies on minor irrigation projects have employed the conventional benefit-cost analysis (BCA) tool to evaluate economic viability and equity considerations of alternative water allocation measures under a variety of climate-related uncertainty [36][37][38][39]. BCA tool has also been widely used in other fields of investment decisions, for instance, renewable energy resource projects [40][41][42] and transportation projects [43,44]. Most of the studies on water resources limited their analysis on the benefit side to estimates of the increase in water use, increase in crop yields, and likely increase in crop areas.…”
Section: The Context Of This Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Past studies on minor irrigation projects have employed the conventional benefit-cost analysis (BCA) tool to evaluate economic viability and equity considerations of alternative water allocation measures under a variety of climate-related uncertainty [36][37][38][39]. BCA tool has also been widely used in other fields of investment decisions, for instance, renewable energy resource projects [40][41][42] and transportation projects [43,44]. Most of the studies on water resources limited their analysis on the benefit side to estimates of the increase in water use, increase in crop yields, and likely increase in crop areas.…”
Section: The Context Of This Studymentioning
confidence: 99%
“…Furthermore, as mentioned before, the future performance of local water resources projects is highly uncertain. Following Yang et al (2007) [43] and Khazraeian and Hadi (2018) [44], we consider multiple sources of uncertainty into the traditional BCA by expressing various model parameters as probability distributions instead of fixed values. The probabilistic BCA is conducted using the popular Monte Carlo simulation technique wherein the analysis is repeated with thousands of sets of parameters representing underlying variability over the life of the project [45,46].…”
Section: The Context Of This Studymentioning
confidence: 99%
See 1 more Smart Citation
“…This method can overcome the limitation of the dimensionality of some previous algorithms in solving American option pricing problems, and can quickly solve the high Victoria American option pricing problem [8]. In addition, we introduce several martingale process construction methods and then give the specific steps of the dual method to solve the American option pricing problem [9]. The results of numerical experiments show that the combination of the quasi-Monte Carlo method and the dual method is obtained, and the calculated results are accurate and require a short time, which can greatly improve the computational efficiency of Monte Carlo simulation, so this method is very effective in practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The upper and lower limits for these input variables were estimated based on the reported values in previous studies. Khazraeian and Hadi ( 5 ) reported that stochastic ROI analysis using a Monte Carlo simulation is a better approach compared with other methods such as the Black Scholes and Binomial Lattice in accounting for uncertainty in the parameters.…”
mentioning
confidence: 99%